The Influence of Self-Assessment on the English Language Learning Process - Herrera, Leonardo; Cuesta Melo, Carlos Hernán; Lucero Zambrano, María Alejandra (Colombian Applied Linguistics Journal, 2022)
Assessment is considered to be a reliable and valid means through which the effects of both teaching and learning can be measured. The lack of research studies in relation to self-assessment in the English Language Teacher Education Program (henceforth ELT Education Program) targeted in this study evidence that no policy determines how learners can self-assess their learning process. For that reason, we conducted this qualitative-descriptive case study that relies on principles of postmodern perspectives and constructivist theories that advocate the construction of learners' knowledge. The main objective was to determine how self-assessment influences the language learning process of a group of students from the ELT Education Program. To respond to this inquiry, we collected data through student reflective journals, focus group discussion commentaries, and an interview to analyze participants' reflections upon their English learning process. The results showed a positive response from students towards reflection. According to their comments, self-assessment evaluates more profound aspects of the self, such as autonomy, self-recognition, critical thinking, persistence, and self-efficacy. They also highlighted the role of reflective journals and focus group discussions as facilitators to self-evaluate deeply and promote collective reflection.